Targeting calcium-mediated inter-organellar crosstalk in cardiac diseases. (3rd April 2022) - Hulsurkar, Mohit M.; Lahiri, Satadru K.; Karch, Jason; Wang, Meng C.; Wehrens, Xander H.T.
ABSTRACT: Introduction: Abnormal calcium signaling between organelles such as the sarcoplasmic reticulum (SR), mitochondria and lysosomes is a key feature of heart diseases. Calcium serves as a secondary messenger mediating inter-organellar crosstalk, essential for maintaining the cardiomyocyte function. Areas covered: This article examines the available literature related to calcium channels and transporters involved in inter-organellar calcium signaling. The SR calcium-release channels ryanodine receptor type-2 (RyR2) and inositol 1, 4, 5-trisphosphate receptor (IP3 R), and calcium-transporter SR/ER-ATPase 2a (SERCA2a) are illuminated. The roles of mitochondrial voltage-dependent anion channels (VDAC), the mitochondria Ca 2+ uniporter complex (MCUC), and the lysosomal H + /Ca 2+ exchanger, two pore channels (TPC), and transient receptor potential mucolipin (TRPML) are discussed. Furthermore, recent studies showing calcium-mediated crosstalk between the SR, mitochondria, and lysosomes as well as how this crosstalk is dysregulated in cardiac diseases are placed under the spotlight. Expert opinion: Enhanced SR calcium release via RyR2 and reduced SR reuptake via SERCA2a, increased VDAC and MCUC-mediated calcium uptake into mitochondria, and enhanced lysosomal calcium-release via lysosomal TPC and TRPML may all contribute to aberrant calcium homeostasis causing heart disease. While mechanisms of this crosstalk need to be studied further, interventions targeting these calcium channels or combinations thereof might represent a promising therapeutic strategy.